2010
DOI: 10.1016/j.gca.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Calcium promotes cadmium elimination as vaterite grains by tobacco trichomes

Abstract: In tobacco plants, elimination of Zn and Cd via the production of Ca-containing grains at the top of leaf hairs, called trichomes, is a potent detoxification mechanism. This study examines how Cd is incorporated in these biominerals, and how calcium growth supplement modifies their nature. Scanning electron microscopy coupled with energy dispersive X-ray microanalysis (SEM-EDX), microfocused X-ray diffraction (l-XRD), and microfocused X-ray absorption near edge structure (l-XANES) spectroscopy were used to ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 98 publications
0
24
0
Order By: Relevance
“…4. Valid speciation information can be obtained by performing PCA and LCF analyses on the spectra of the sorption samples (Ressler et al, 2000;Isaure et al, 2010). In this study, PCA was performed to define the number of components in the normalized spectra of the eight sorption samples and the results revealed that two significant components accounted for 91% …”
Section: Xanes Spectroscopy Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…4. Valid speciation information can be obtained by performing PCA and LCF analyses on the spectra of the sorption samples (Ressler et al, 2000;Isaure et al, 2010). In this study, PCA was performed to define the number of components in the normalized spectra of the eight sorption samples and the results revealed that two significant components accounted for 91% …”
Section: Xanes Spectroscopy Analysismentioning
confidence: 99%
“…Recently, X-ray absorption spectroscopy (XAS) has been increasingly applied to investigate the sorption mechanisms and speciation of trace elements in mineral and plant samples (Randall et al, 1999;Waychunas et al, 2003;Gräfe et al, 2007;Isaure et al, 2010). Particularly, X-ray absorption near edge structure (XANES) spectroscopy is expected to meet the need of the detection limit and provide the information of complexation and speciation of Cd in environmental samples (Waychunas et al, 2003;Gräfe et al, 2007;Isaure et al, 2010). To our knowledge, it has not been used so far to investigate Cd sorption reactions in red mud probably due to the limits of high energy required by K-edge and low sensitivity at L III -edge of Cd absorption spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The monochromatic beam of the ID21 beamline was focused with the zoneplate (0.3 × 0.7 μm 2 ) for the Cd L 3 -edge μ-XANES measurements in the apoplast and symplast, while in the phloem region and for the Cd model compounds, the beam was focused with a pinhole of 50 and 100-μm diameter, respectively. The exact energy calibration was established with absorption measurements on a 2-μm-thick Cd metal foil, measured in transmission mode, by assigning the first inflection point of the Cd L 3 edge of the Cd foil to 3,538 eV (Isaure et al 2006(Isaure et al , 2010.…”
Section: Co-localisation Analysismentioning
confidence: 99%
“…The Cd in the plant cells was expected to be bound to different organic ligands, so the most probable candidates were selected in a set of reference compounds on the basis of the existing literature (Isaure et al 2006(Isaure et al , 2010. The relative amounts of the Cd ligands at the selected point in the cell was determined with the linear combination fit method (Ravel and Newville 2005), where the Cd L 3 -edge μ-XANES spectra measured in the plant cells were modelled with a linear combination with the Cd L 3 -edge μ-XANES spectra of the chosen reference Cd compounds (Isaure et al 2006(Isaure et al , 2010. In all of these cases, the best fit was obtained with the spectrum of Cd-glutathione (Cd-S-C-R coordination) and the spectrum of Cd-pectin (Cd-O-C-R coordination).…”
Section: (Red) -S (Green) CD (Red) -Cl (Green) Cd (Red) -P (Green)mentioning
confidence: 99%
“…Then, Cd ligands were determined by Cd LIII-edge µXANES recorded on various tissues of storage evidenced by µXRF. The XANES and µXANES spectra were then compared to spectra of modelcompounds including Cd minerals, Cd-sorbed minerals and Cd-complexed organic, already collected (Isaure et al, 2006(Isaure et al, , 2010, and fitted by linear combinations of these reference spectra. Chemical mapping and spectroscopy were performed on the beamline LUCIA (Soleil, Saclay, France) in cryogenic conditions to limit artefact from element redistribution and speciation change.…”
Section: Localization and Speciationmentioning
confidence: 99%